A survey of resource sharing among science & technology libraries in Metro Manila, with implications to Nepal - Dahal, Tara M. (1988)
This study surveyed the status of resource sharing among the science and technology (S & T) libraries in Metro Manila and looked into its special implications for similar activities in Nepal. Out of 60 libraries, only 23 comprised the sample which includes 16 government libraries, five private corporation libraries and two regional or international libraries.